Efektivitas Kegiatan Simpan Pinjam Khusus Bagi Kaum Perempuan Rumah Tangga Miskin di Kecamatan Denpasar Timur - Arnaya, Putu Yudi; Suyana Utama, Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 1, No. 1, November 2012 (pp. 1-60), 2012)
The research was meant for knowing how to rate the effectiveness of women's savings and credit activities of poor households in the district denpasar eastern city of Denpasar. Effectiveness is measured activities of a variable input, process and output. The method of analysis used in this study is a quantitative method / math simple, descriptive analysis and factor analysis. The data used are primary data of poor households (RTM) which is supported by as many as 440 and as many samples taken 88 people. Based on the research activities of the Women's Savings and Loans (SPP) in the District of East Denpasar, Denpasar said to be very effective in the amount of 84.20 percent, and of the three studied variables that contributed most to the effectiveness of the activities of the Women's Savings and Loans (SPP) in the District East Denpasar, Denpasar is the effectiveness of the input.
Keywords: Effectiveness; Women; Poverty; Family; Income; SPP